Preliminary Psychometric Evaluation of the Hamilton Depression Rating Scale in Methamphetamine Dependence. Issue 4 (2nd October 2017) - Hellem, Tracy; Scholl, Lindsay; Sung, Young-Hoon; Ferguson, Hayden; McGlade, Erin; Yurgelun-Todd, Deborah; Renshaw, Perry; Hildreth, Laura
ABSTRACT: Objective : The purpose of this study was to test the initial psychometric properties of the 17-item Hamilton Depression Rating Scale (HAM-D) in individuals with and without major depressive disorder who use methamphetamine. We used data from two completed studies and two ongoing clinical trials. The HAM-D has well established reliability and validity in a variety of populations. However, there are no published reports of reliability and validity of the HAM-D in a methamphetamine-using population.Methods : HAM-D and depression status data were extracted from four separate studies for this psychometric assessment. Using these data, we evaluated three measures of construct validity: internal consistency, contrasted group validity, and factorial validity.Results : We found potential concerns with the construct validity of the HAM-D in users of methamphetamine. Intercorrelations between items were primarily less than 0.20 and the Cronbach's alpha value in this sample was 0.58, indicating potential issues with internal consistency. The results of two-sample t -tests suggest concerns with contrasted group validity, as no significant difference in average scores were found for nine items. Consistent with previous studies, a principal component analysis indicates that the HAM-D is multidimensional.Conclusions : The 17-item HAM-D might not reliably and validly measure depression severity in a methamphetamine-using population. Given our small sample, additional research is needed, though, to further test the psychometric properties of the HAM-D in individuals who use methamphetamine.